Polyacrylic Acid Supported L-proline as an Effective Heterogeneous Catalyst for the Direct Asymmetric Aldol Reaction - Zhang, Cuizhi; Fan, Yanchao; Wang, Sijia; Liu, Shaojie; Chu, Xiaomeng; Tang, Erjun (Current Organic Synthesis, 2024)
Introduction: L-proline is an efficient chiral small-molecule organocatalyst for the direct asymmetric aldol reaction between unmodified acetone and a variety of aldehydes. Methods: However, it is difficult to separate from the reaction medium for reuse. In this work, polyacrylic acid (PAA) supported The acylation reaction between L-hydroxyproline and PAA prepared lproline (P(AA-co-PA)) catalysts with various catalyst loadings. Fourier characterized them transforms infrared spectroscopy, nuclear magnetic resonance spectrum, gel permeation chromatography and thermogravimetry analysis. Results: These macromolecular catalysts were used to catalyze acetone and benzaldehydes' direct asymmetric aldol reaction. The influence of the catalyst structure on the catalytic performance was studied, and the reaction conditions were optimized. Conclusion: The results showed that P(AA-co-PA) with 50 mol% catalyst loading had excellent catalytic performance, much higher than that of L-proline and L-hydroxyproline. Its recovery was achieved by simple filtration. After being reused 7 times, its catalytic performance was still higher than that of L-proline.
Keywords: L-proline